Optimization of in situ forming intragastric oral formulations with different grades of PEGs - Patel, RR; Patel, JK (Ars Pharmaceutica (Internet), 2011)
The drug release profiles were optimized using different grades of polyethylene glycols (PEGs). Phase diagrams of ternary mixtures of ethylcellulose, PEG and TEC were obtained and used for optimization of drug release. The phase diagrams showed that addition of higher molecular weight of PEGs increased the phase separation and caused precipitation of ethylcellulose from the ternary mixtures. The effect of different grades and concentrations of PEGs in novel oral intragastric controlled release gel formulations were also investigated. In conclusion, the in situ forming oral controlled release formulations were successfully developed and the formulations were able to control the release of hydrochlorothiazide up to 24 hours.